CYCLE TOURISTS IN THE EUROPEAN CIRCUIT VALLEY – SANTA CATARINA: PROFILE, TRAVEL HISTORY AND MOTIVATIONS (Fiep Bulletin - online, 2013)
The cycling can be defined as travel by bicycle. In Brazil, Santa Catarina state which developed the first cycling experience. This is still a growing segment, therefore, the construction of knowledge in the area is still small. Contributions are needed in this area to strengthen the theoretical field and also to guide entrepreneurs in the tourism business. The aim of this study was to identify the profile of cicloturista, your travel history and their motivations for Velotour 2012 in Circuit European Valley in Santa Catarina. The sample consisted of 38 individuals participating in the Velotour 2012. The results show that most of the participants are male, has between 30 and 39 years old and lives in São Paulo. 26% of participants Velotour cyclists are 1-3 years and 31% of respondents this was the first bike trip. 68% of respondents began practicing for leisure / physical activity. The main motivation is to join Velotour tourism / leisure then to make new friends.
Keywords: Cycling; Leisure; Motivations